2016
DOI: 10.3390/cancers8060055
|View full text |Cite
|
Sign up to set email alerts
|

RASSF1A Site-Specific Methylation Hotspots in Cancer and Correlation with RASSF1C and MOAP-1

Abstract: Epigenetic silencing of RASSF1A is frequently observed in numerous cancers and has been previously reported. The promoter region of RASSF1A is predicted to have 75 CpG sites, and very few studies demonstrate how the methylation of these sites affects expression. In addition, the expression relationship between RASSF1A and its downstream target, modulator of apoptosis 1 (MOAP-1), is poorly understood. In this study, we have explored the mRNA expression of RASSF1A, MOAP-1 and the well-characterized splice varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Our research group has demonstrated that RASSF1A can restrict NOD2-RIPK2 association in intestinal cells to subsequently interfere with the ability of RIPK2 to drive NF-κB-directed molecular inflammation [ 43 ]. Epigenetic analysis via pyromark sequencing of 32 CpGs of the RASSF1A promoter region revealed that IBC patients have a higher percentage of CpG methylation in comparison to breast reduction surgery (BRS) patients (normal control) [ 67 ]. Similar to most solid cancers, high methylation of RASSF1A in IBC patients correlates with loss of expression [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research group has demonstrated that RASSF1A can restrict NOD2-RIPK2 association in intestinal cells to subsequently interfere with the ability of RIPK2 to drive NF-κB-directed molecular inflammation [ 43 ]. Epigenetic analysis via pyromark sequencing of 32 CpGs of the RASSF1A promoter region revealed that IBC patients have a higher percentage of CpG methylation in comparison to breast reduction surgery (BRS) patients (normal control) [ 67 ]. Similar to most solid cancers, high methylation of RASSF1A in IBC patients correlates with loss of expression [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MOAP-1 may be regulated by phosphorylation as several phosphorylation sites have been identified in MOAP-1 protein sequence [29]. Analysis of MOAP-1 gene led to the identification of CpG island located near the gene promoter of MOAP-1, pointing to the possibility that MOAP-1 might be regulated through hyper-methylation of its gene promoter [106]. Other than gene expression regulation, pro-apoptotic activity of MOAP-1 was reported to be regulated by members of PNMA family.…”
Section: Regulation By Other Mechanismsmentioning
confidence: 99%
“…RASSF1A, arguably the most frequently silenced tumor suppressor in human cancer (31,32,34), is another member of the RASSF family that plays an important role in β-Catenin signaling (32). Studies by Ram and colleagues showed that RASSF1A interacts with β-TrCP, and that the down-regulation of RASSF1A led to the stability of β-catenin (94), as is the case with NORE1A (83).…”
Section: Nore1a Forms a Ras-regulated Complex With β-Trcp And Suppresmentioning
confidence: 99%
“…Notably, most RASSF family members are down-regulated in human cancers, in part by epigenetic mechanisms (32). The best characterized member, RASSF1A, is now thought to be the most frequently silenced tumor suppressor in human cancers, highlighting the significance of this family in tumor suppression (31,33,34). …”
Section: Introductionmentioning
confidence: 99%